Towards Clinically Relevant Oculomotor Biomarkers in Early Schizophrenia - Athanasopoulos, Fotios; Saprikis, Orionas-Vasilis; Margeli, Myrto; Klein, Christoph; Smyrnis, Nikolaos (Frontiers in Behavioral Neuroscience, 2021)
In recent years, psychiatric research has focused on the evaluation and implementation of biomarkers in the clinical praxis. Oculomotor function deviances are among the most consistent and replicable cognitive deficits in schizophrenia and have been suggested as viable candidates for biomarkers. In this narrative review, we focus on oculomotor function in first episode psychosis, recent onset schizophrenia as well as individuals at high risk for developing psychosis. We critically discuss the evidence for the possible utilization of oculomotor function measures as diagnostic, susceptibility, predictive, monitoring and prognostic biomarkers for these conditions. Based on the current state of research we conclude that there are not sufficient data to unequivocally support the use of oculomotor function measures as biomarkers in schizophrenia.